A research protocol for studying participatory processes in the use of evidence in child welfare systems. (1st August 2019) - Metz, Allison; Boaz, Annette; Powell, Byron J
Abstract : This paper presents a protocol for a funded study of technical assistance strategies used to support the use of evidence, and, in particular, how participatory processes contribute to the use of evidence to improve outcomes for populations. Findings from the study will increase understanding of the relationships between technical assistance, stakeholder participation and evidence use in child and family services. The authors argue that publishing such a protocol can increase transparency between researchers and practitioners and raise awareness of the need for research on how stakeholder participation can strengthen evidence use in child welfare service settings. The authors also reflect on the potential value and limitations of published protocols. This study will systematically gather input from stakeholders with expertise in technical assistance to develop a compilation of strategies that can be used to support the use of evidence. The study will identify strategies that include stakeholder involvement and assess which strategies under what conditions facilitated the use of research evidence. The study will address four research questions: What technical assistance strategies are used to support the use of research evidence? What are the consensus-driven terms and definitions of identified strategies? To what extent do technical assistance strategies involve stakeholders and for what purpose?